Practical understanding of the operating principle of digital communication systems - Gebrehiwet Gebrekrstos Lema; Teklehaymanot Baweke Reda; Dawit Hailu; Tole Sutikno (Institute of Advanced Engineering and Science, 2019)
There are many students and researcher who doesn’t really understand the practical operating principle of digital communication system. Hence in this paper, the digital communication system is studied and simulated. In the system kit development text and audio inputs are taken and encrypted with different encryption techniques including additive cipher, multiplicative cipher and affine ciphers. The encrypted data is converted in to an 8-bit binary, channel encoded with distinct channel coding styles like linear block encoder, cyclic encoder and convolutional encoder, line coded and band pass modulated by different digital modulation techniques. Finally, the developed software is tested with equivalent inputs of the current national TV broadcasting and the results found are correct according to the theoretical analysis of the discussion.